Studies of Dº→Kºsh+h'- decays at the LHCb experiment - Lupton, O (2016)
This thesis documents two studies of the neutral charm meson system using the LHCb detector, and gives an overview of the numerous changes made to the LHCb software trigger in advance of Run 2 of the LHC. In the first analysis, amplitude models are applied to studies of the resonance structure in D0 → K0SK−π+ and D0 → K0SK+π− decays using proton-proton collision data, corresponding to an integrated luminosity of 3.0 fb−1, collected during Run 1 of the LHC. Relative magnitude and phase information is determined, and coherence factors and related observables are computed for both the whole phase space and a restricted region of 100 MeV/c2 around the K*(892)± resonance. Two formulations for the Kπ S-wave are used, both of which give a good description of the data. The ratio of branching fractions B (D0→ K0SK+π−) /B (D0→ K0SK−π+) is measured to be 0.655 ± 0.004 (stat) ± 0.006 (syst) over the full phase space and 0.370 ± 0.003 (stat) ± 0.012 (syst) in the restricted region. A search for CP violation is performed using the amplitude models and no significant effect is found. Predictions from SU(3) flavour symmetry for K*(892)K amplitudes of different charges are compared with the amplitude model results, and marginal agreement is found. The second study estimates the sensitivity to D0–D̄0 mixing and indirect CP violation parameters that can be achieved using a model-independent technique and the samples of D0→ K0SK+K− decays recorded by LHCb in Run 1 and Run 2 of the LHC. These studies show that constraints on these parameters could be significantly improved by an analysis of the anticipated Run 2 dataset.